Analisis Keterlibatan Dan Keamanan Kerja Terhadap Intensi Turnover Karyawan Outsourcing Millenial Melalui Kepuasan Kerja (Studi Empiris Pada Divisi Sentra Operasi (STO) Kantor Pusat PT Bank Rakyat Indonesia Tbk.) - Rahmawati, Andi; Khurosani, Aan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
This paper is to answer the relationship between work attachment and job security to turnover intentions that are intervened by job satisfaction at the Operations Center Division of PT Bank Rakyat Indonesia Headquarters. The purpose of this study was to examine and analyze the relationship between work engagement and job security on turnover intentions intervened by job satisfaction. This type of research is quantitative research with data analysis Structural Equation Modeling (SEM) with data processing using SmartPLS 3.0. The population in this study were 175 employees with a sample of 75 respondents using random sampling techniques. The result of this study is that there is no insignificant negative influence between job involvement and job satisfaction on turnover intention. However, there is a negative and significant influence between job security on turnover intention. In addition, job involvement and job security have a positive and significant effect on job satisfaction.